MODIFICATION OF COUNTERCULTURAL GROUPS IN MODERN SOCIETY - Новак, Т. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article researches the modification of countercultural groups in informational society.